Microlending in emerging economies: Building a new line of inquiry from the ground up - Bruton, Garry D; Khavul, Susanna; Chavez, Helmuth (Journal of International Business Studies, 2011)
The world's poor may be the last great frontier in international business. International microlenders are increasingly tapping into this emerging opportunity by extending small business loans to millions of borrowers. However, to date, there is very limited understanding of this domain from an international business perspective. Using qualitative case studies developed in Guatemala and the Dominican Republic we probe the causes and consequences of high performance and business failure for microloan recipients. The analysis of these cases led to the development of six testable propositions focused on the behavior of borrowers whose loans populate the portfolios of international microlenders. Our research aims to lay a foundation in international business for future research on microlending.